Analisis Kelayakan Operasional Penyediaan Fasilitas Rekreasi Anak untuk Peningkatan Level of Service di Bandar Udara - Ravi Al Farkhan; Hanif Pradana; Ozwaldo Henriques; Elfi Amir; Rany Adiliawijaya Putriekapuja (Jurnal Kendali Teknik dan Sains, 2025)
This study aims to analyze the operational feasibility of providing child-friendly recreational facilities at airport terminals to enhance service quality or Level of Service (LoS). A qualitative approach based on a literature review was used to examine various sources and previous research to evaluate the urgency, impact, as well as design and implementation strategies for child-friendly facilities at airports. Facilities such as play areas, breastfeeding rooms, and child-friendly toilets are expected to improve the experience of passengers, particularly families traveling with children, by providing additional comfort during their time at the airport. The findings indicate that the presence of these facilities significantly contributes to improving user perceptions of the airport’s service quality. The psychological comfort of family passengers is also enhanced, with safe and comfortable spaces for children. This not only creates a more inclusive environment but also provides operational benefits such as better terminal space management and efficiency. Child-centered design plays a crucial role in improving facility quality, where modular design is seen as a practical solution to adapt the facilities to the evolving needs of the terminal. Moreover, collaboration with private sectors is considered a strategic approach to support the provision of these facilities, given the substantial investment required. The study concludes that investing in child-friendly facilities at airports is a strategic decision, as it has the potential to enhance the airport's competitiveness. Well-designed facilities also improve user satisfaction and create a more comfortable travel experience. These findings are expected to serve as a reference for airport managers and provide a foundation for future research that quantitatively measures the impact of these facilities.